2005
DOI: 10.1121/1.4785822
|View full text |Cite
|
Sign up to set email alerts
|

Lexical frequency effects and phonetic duration of English homophones: An acoustic study

Abstract: Some current views of phonology assume a single abstract representation for each lexical item, while others assume extensive encoding of fine-grained detail. Some proponents of the latter view have claimed that differences in lexical (token) frequency are manifested as differences in phonetic duration. This claim was investigated in three experiments measuring the phonetic durations of heterographic pairs of homophonous English nouns differing in token frequency. Homophonous pairs were grouped according to mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In a corpus study of child-directed speech, Conwell (2017a) reported that adults differentiate homophone meanings as a function of frequency when speaking to children, but only in utterance-final positions, which is consistent with the findings from Cohn and colleagues (2005). Additionally, Conwell (2017a) found that higher frequency homophone meanings in child-directed speech had higher mean pitch than their lower frequency counterparts.…”
supporting
confidence: 69%
“…In a corpus study of child-directed speech, Conwell (2017a) reported that adults differentiate homophone meanings as a function of frequency when speaking to children, but only in utterance-final positions, which is consistent with the findings from Cohn and colleagues (2005). Additionally, Conwell (2017a) found that higher frequency homophone meanings in child-directed speech had higher mean pitch than their lower frequency counterparts.…”
supporting
confidence: 69%
“…While most previous studies do not disclose all homophone pairs analyzed (Whalen 1991, Guion 1995, Cohn et al. 2005, Gahl 2008, 2009), judging from the examples that are discussed, the homophones analyzed were homonyms, i.e. unrelated semantically, e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Guion (1995) reports a similar positive finding for homophones embedded in constructed sentences, but a negative finding when the words were pronounced in citation form in generic carrier phrases. Cohn et al (2005) fail to find an effect of lemma frequency on duration, testing the pronunciation of homophones both in constructed sentences and also read off lists. All of the experimental studies tested heterographic homophones.…”
Section: The Present Study In the Context Of Previous Research About mentioning
confidence: 92%
See 2 more Smart Citations